Principales factores que producen fragilidad cromosómica transitoria en los pacientes referidos para estudio citogenético - Escribano R., Gloria; Castillo T., Silvia; Daher N., Vera; Salazar C., Samuel; Tobella P., Lorena (Revista Hospital Clínico Universidad de Chile, 2009)
The fragile sites are specific loci that show fractures during karyotyping perform under specific laboratory conditions. Are present in normal individuals and are classified by their population frequency. These sites have been associated with an increase in chromosome fragility, fractures and other chromosomal abnormalities. In recent years, the fragile sites have taken great importance because they represent regions in the genome that are particularly sensitive to replicative stress and are frequently rearrenged in tumor cells. Multiple risk factors endogenous and exogenous have been involved in the increase in chromosome fragility, including microorganisms, drugs, illegal drugs and toxins. The fragile sites have provided insight into understanding of the effects of replicative stress on DNA damage and genomic instability in cancer cells. In this work we aim to summarize the limited information available about the topic, and the clinical significance of fragile sites in vivo in the laboratory